Bibliometric analyses of climate psychology: critical psychology and climate justice perspectives - Anjum, Gulnaz; Aziz, Mudassar (Frontiers in Psychology, 2025)
The psychology of climate change has become a critical area of research, exploring the intersection between human behavior, psychological wellbeing, and environmental sustainability. This paper presents a bibliometric analysis to explore the interdisciplinary field of psychology and climate change, covering research from 01 January 1995 to 15 August 2024. Using 3,087 academic publications from the Web of Science and employing VOSviewer and BiblioMatrix for network analysis, we dissect the evolution, key contributors, and central themes within this domain. Our analysis identifies leading authors, institutions, and nations, alongside the collaboration networks underlying the field’s growth. Thematic clustering of these networks highlights dominant topics such as pro-environmental behavior, sustainability, mental health, eco-anxiety, and risk perception. We utilize visual mappings of co-authorship and bibliographic relationships to illustrate the dynamic interaction among researchers and their topics. By framing our findings through the lens of climate justice and critical psychology, we advocate for a research paradigm that challenges systemic barriers to climate justice, emphasizing the necessity for equitable and action-oriented psychological research to guide climate-related policy and public engagement.